Analysis and experiment of a positioning and pointing mechanism based on the stick–slip driving principle - Zhu, Yongqi; Li, Juan; Huang, Jianbin; Li, Weida; Liu, Gai; Sun, Lining (Frontiers in Neurorobotics, 2025)
IntroductionTraditional positioning and pointing mechanisms often face limitations in simultaneously achieving high speed and high resolution, and their travel range is typically constrained. To overcome these challenges, we propose a novel positioning and pointing mechanism driven by piezoelectric ceramics in this study. This mechanism is capable of achieving both high speed and high resolution by using two driving principles: resonance and stick–slip. This paper will focus on analyzing the stick–slip driving principle.MethodsWe propose a configuration of the drive module within the positioning and pointing mechanism. By applying a low-frequency sawtooth wave excitation to the piezoelectric ceramics, the mechanism achieves high resolution based on the stick–slip driving principle. First, a simplified dynamic model of the drive module is established. The motion process of the drive module in stick–slip driving is divided into the stick phase and slip phase. With static and transient dynamic analyses conducted for each phase, the relationship between the output shaft angle, resolution, and driving voltage is derived. It is observed that during the stick phase, the output shaft angle and the driving voltage exhibit an approximately linear relationship, while in the slip phase, the output shaft angle and the driving voltage display nonlinearity due to impact forces and vibrations. Finally, a prototype of the positioning and pointing mechanism is designed, and an experimental platform is constructed to test the resolution of the prototype.ResultsWe construct a prototype of a dual-axis positioning and pointing mechanism composed of multiple drive modules and conduct resolution tests using two control methods: synchronous control and independent control. When synchronous control is used, the output shaft achieves a resolution of 0.38μrad, while with independent control, the resolution of the output shaft reaches 0.0276μrad.DiscussionThe research results show that the positioning and pointing mechanism proposed in this study achieves high resolution through stick–slip driving principle, offering a novel approach for the advancement of such mechanisms.